Governing Ecological Value in China: State-Created Markets and Public Value - Chao Huang; Hao Liu; Lin Ma (Land, 2026)
How can public authorities make ecological resources governable and economically actionable without reducing nature to an ordinary commodity? This study examines ecological product value realization (EPVR) in China through 58 official domestic cases. Constructivist grounded-theory coding, Gioia-style data structuring, cross-batch mapping, documentary triangulation, and coding-consistency checks identify five recurrent and interdependent governance functions: institutional recognition, value articulation, governed market construction, collaborative mobilization, and public-value recirculation. These functions are empirically recursive rather than sequential. Recognition constitutes ecological resources and rights as governable objects; articulation makes plural ecological contributions communicable; market construction creates bounded conditions for exchange; collaborative mobilization assembles implementation capacity; and recirculation links captured value to ecological reinvestment, community benefit, and accountability. Cross-batch comparison provides qualified evidence that later demonstration repertoires increasingly incorporate multi-resource portfolio governance. The study contributes to land governance and public policy by conceptualizing EPVR as governed value translation. The framework further distinguishes value realization from value capture and public value creation: making ecological value actionable or generating financial returns does not by itself establish public value unless ecological integrity, distributive legitimacy, and accountability are secured. A public-policy architecture is one in which ecological markets are institutionally constructed and remain subject to ecological, distributive, and accountability constraints. Public value is treated as the normative outcome criterion, while recirculation is a feedback function that can connect value capture to that criterion.